Dukungan Lingkungan Sosial Berhubungan dengan Perilaku Merokok pada Remaja - Laila Zumrotussholikhah; Nutrisia Nu’im Haiya; Iwan Ardian (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Social support is an important determinant of adolescent health behavior and plays a role in shaping their tendencies towards risky behaviors, including smoking. Interactions with family, peers, and media exposure have the potential to influence their perceptions, judgments, and decisions to smoke. This study aims to analyze the relationship between social support and smoking behavior in adolescents. Methods cross-sectional design, total sampling of 133 respondents, consisting of all ninth-grade male students. The study variables were social support and smoking behavior. Data were collected using a questionnaire from July to September 2025. Results most respondents had good social support (65.4%), and the majority did not smoke (60.9%). Chi-square analysis showed a significant relationship between social support and smoking behavior in adolescents (p-value = 0.001), where adolescents with poor social support were at greater risk of smoking. Conclusion social support influences adolescents' tendency to smoke.